MEDIATIZATION OF ISLAMIC DA‘WAH ON SOCIAL MEDIA: THE AUTHORITY OF ULAMA AND AUDIENCE LEGITIMATION IN DIGITAL SPACES - Rudi Trianto; saparwadi-ntb; Agus Nurhadi (TASAMUH : Jurnal Komunikasi dan Pengembangan Masyarakat Islam, 2026)
This study aims to examine the mediatization of Islamic da‘wah on social media, with a particular focus on the transformation of ulama authority and audience legitimation in digital spaces. This research employs a literature review method with a qualitative-descriptive approach to studies on digital religion, the mediatization of religion, da‘wah communication, religious authority, digital ulama, religious influencers, and social media audience reception. The findings indicate that social media does not merely function as a channel for disseminating da‘wah messages, but also reshapes the ways in which Islamic da‘wah is produced, packaged, distributed, and legitimized. The authority of ulama no longer rests solely on chains of scholarly transmission, religious institutions, organizational hierarchies, or recognition from traditional communities. It is also shaped by digital visibility, communicative performativity, visual aesthetics, platform interactivity, and audience engagement. In digital spaces, audiences play an active role in shaping the legitimacy of da‘wah through following, liking, commenting, sharing, criticizing, and constructing the public image of ulama. These findings affirm that the mediatization of Islamic da‘wah gives rise to religious authority that is relational, participatory, and digitalized. This article concludes that the transformation of Islamic da‘wah on social media is not merely a shift of medium from the physical pulpit to digital platforms, but a process of reconfiguring religious communication involving ulama, the logic of social media, algorithms, and audiences as actors of legitimation.